Dried Fruit Jams (Dates and Raisins) / Siti Nur Atiqah Sukri - Siti Nur Atiqah, Sukri (2020)
Kisma Enterprise is a company that offers food products which name as Yummy Tummy that has a long lasting period and high in nutrient as it made of dates and raisins which suitable to be taken in order to stay full and healthy. This food product is very easy to handle , to serve and suitable to be consume with bread. Yummy Tummy is also offered to all stage of community groups and can be as home food stocks. In addition, this product is also available to all customers at affordable price and high in quality. Besides, with a medium size of its packaging, it easy to bring whenever want to travel. Yummy Tummy is also contain with 100% of pure dates and raisins which give a best taste of jams to every consumers. This product has a high potential to growth as it made of fruit which can be eat by every religion. So, the changes for this product to gain high profit is high and it can be one of the favourite jams for the consumers. Other than that, the difference of Yummy Tummy compared to the others product is the uniqueness of its taste which cant be found from another product. This is because this product has never been produce by any firm so the unique of its taste can only be found in this Yummy Tummy. Hence, the potential for this product to grow further is bigger and the great of its taste will always loved by the consumers. The profitability of this product can be enhanced by the supportive results from the local people. Therefore, the marketing management will always ensure that this product will be known by the whole community of the country in order to achieve the high sales and profit.